Análise do processo de cooptação do lançamento da marca Love, Beauty and Planet no mercado vegano - Lemos, Marina Fornielles (Universidade do Vale do Rio dos Sinos, 2021)
The goal of this essay is to understand the strategy adopted by the vegan cosmetics brand Love, Beauty and Planet by Unilever in an attempt to develop the co-optation process with the vegan market. Therefore, this paper seek to: analyze the digital strategies and tactics performed by Love, Beauty and Planet; understand the role of digital influencers in forming consumer perception; comprehend the relationship and perception of consumers with the Love, Beauty and Planet brand and evaluate Love, Beauty and Planet's co-optation capacity and the vegan movement. The methodological strategy that guided this study involved the multi-method approach of exploratory study, applied to a case study. The research involved an in-depth interview with the brand's marketing manager in Brazil, desk research and participatory observation of the brand's profile on Instagram, as well as profiles of digital influencers and consumers. The gathered information was analyzed by the content analysis technique. The results indicate that Love, Beauty and Planet performed its communication strategy in a way that is out of line with the principles of veganism, so that, even acquiring the seal of regulatory bodies and endorsement by powerful digital influencers, it did not consolidate its co-optation process. In this way, Love, Beauty and Planet can demonstrate that the legitimacy strategy wrongly anchored in digital influencers discredits the brand and the influencers themselves, since the consumer's perception of the endorsed product is higher than expected.
Keywords: Cooptação; Influenciadores digitais; Veganismo; Cosméticos veganos; Co-optation; Digital influencers; Veganism; Vegan cosmetics; ACCNPQ::Ciências Sociais Aplicadas::Administração